Perception and Analysis of Existing Practices Associated with Risk of Brucellosis among Dairy Farmers - Verma, A P; Meena, H R; Lal, S P; Kumar, Vikash; Gupta, B K; Mishra, Dheeraj; Ojha, P K; Mishra, B P (Indian Journal of Extension Education, 2023)
The study to measure the perception and identify risky practices at the farm and household level on commercial dairy farms in six districts of Haryana and Punjab states was conducted during 2018-19. Dairy farmers’ responses were obtained through an interview using a well-structured interview schedule. Univariate Logistic regression models were used to analyze the potential predictors for the risky behaviours of respondents. Binary logistic analysis revealed that Wald statistics values were significant at a 1% level for the explanatory variables viz., education while occupation and herd size were found significant at a 5% level. Half of the respondents (52.50%) had a high perception towards brucellosis disease risk. About one-third of the respondents (28.33%) of the respondents were found in the category of moderate perceptual level. Pearson chi-square indicates that there were significant associations for health status variables such as landholding, annual income, herd size, and milk production with the perception of respondents. Poor understanding of brucellosis, the presence of manifold risky practices, and incorrect perception of respondents need an urgent policy for the prevention and control of brucellosis in farm animals.
Keywords: Practices; Risk factor; Perception; Brucellosis; Dairy farmers